Improving Early Childhood Vocabulary Recognition through Flashcard Media: A Qualitative Study in Kindergarten - Siti Hasanah; lily Yuntina (Qualitative Research in Early Childhood Education, 2026)
This study aimed to explore how the use of flashcard media supports vocabulary recognition among children aged 5–6 years in Group B of Tunas Karya III Kindergarten, Sukanagara, Cianjur. A qualitative case study approach was employed to gain an in-depth understanding of children's learning experiences and teachers' instructional practices during vocabulary learning activities. The participants consisted of ten children, one classroom teacher, and the school principal, who were selected purposively based on their direct involvement in the learning process. Data were collected through classroom observations, semi-structured interviews, field notes, and documentation. The data were analyzed using thematic analysis, including data reduction, data display, and conclusion drawing. The credibility of the findings was ensured through triangulation of data sources, member checking, prolonged engagement, and peer debriefing. The findings revealed three major themes: (1) flashcards increased children's interest and engagement during literacy activities; (2) visual representations on flashcards facilitated children's recognition of letters, sounds, and simple vocabulary; and (3) interactive teacher-child communication strengthened children's confidence in recognizing and pronouncing words. The study concludes that flashcard media provides meaningful learning experiences that promote early vocabulary development and support language acquisition in early childhood education.